PENGATURAN PERLINDUNGAN HUKUM KORBAN DELIK ADAT LOKIKA SANGGRAHA - DEWI, NI MADE LIANA (Fakultas Hukum Universitas Dwijendra, 2016)
ABSTRACTÂ Lokika customs act offenses Sanggraha in Bali, there is no regulation in the various laws and regulations that exist in Indonesia, especially in the Criminal Code so that women as victims do not receive legal protection. Acts cohabiting is an act that is equated with the offense customary lokika Sanggraha so it can be seen in the Emergency Law No. 1 of 1951 Article 5, paragraph (3) sub b, that there are two categories in the formulation of the word